WRITING FABLES TO ENHANCE CREATIVITY OF STUDENTS OF SMPN 48 SURABAYA - Kartiningsih, Rindrah; Pasopati, Rommel Utungga; Wijaya, Kusuma; Andharu, Devito; Fadillah, Muhammad Reza Ishadi; Ananta, Bintang Ryan; Kusuma, Albert Wijaya; Napitupulu, Johanes Claudio Perdana (Asosiasi Dosen Muda Indonesia, 2024)
This article explains the importance of writing fables, especially to uplift their creativity in socio-cultural circumstances. This writing is based on community service done to junior high school students in SMPN 48 Surabaya in 2024. The creative capacities of children possess the potential to enhance their comprehension of individuals, communities, and cultures in everyday experiences, as articulated by Lev Vygotsky. The act of writing fables can serve to enhance creativity, facilitating a deeper exploration of their environmental understanding alongside the improvement of their linguistic competencies. Through an exploratory approach within qualitative research, this manuscript underscores fable writing as a mechanism to cultivate awareness of the students’ potentials, surroundings, and imaginative thoughts pertinent to cognitive development. In conclusion, the practice of writing fables for junior high school students is essential for the advancement of creativity within the realms of formal education and daily life.